Climate Change and Psychological Adaptation: A Behavioral Environmental Economics Approach - Ronnie Schöb; Thomas Aronsson (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2014)
Economic models of climate policy (or policies to combat other environmental problems) typically neglect psychological adaptation to changing life circumstances. People may adapt or become more sensitive, to different degrees, to a deteriorated environment. The present paper addresses these issues in a simple model of tax policy to combat climate change and elaborates on the consequences for optimal climate policies. Furthermore, it argues from a normative point of view that psychological adaptation needs to be taken into account by a pure welfarist government, which aims at internalizing an intertemporal externality.
Keywords: D03; D61; H21; 330